Alan and Naomi - Levoy, Myron (New York : HarperTrophy, 1977)
In New York of the 1940s a boy tries to befriend a girl traumatized by Nazi brutality in France.
6.5
7-10.
Keywords: Friendship -- Fiction; Mentally ill -- Fiction; Friendship -- Fiction; Mentally ill -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction